2007
DOI: 10.1159/000111931
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine as an Alternative Therapeutic Trial in the Therapy of Inappropriate Sinus Tachycardia

Abstract: Inappropriate sinus tachycardia is a disease which is relatively rarely found and sometimes difficult to treat. Up to now it has been mostly treated with a β-blocker or verapamil. If this did not work sinus node modulation was considered. Since the relatively new selective IF-stream blocker ivabradine has been approved for the therapy of chronic stable angina pectoris, a new therapeutic option is available. As ivabradine is well tolerated and only few side effects are known, it may become a new therapeutic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Its mode of action is by blocking the "funny" current (If) responsible for spontaneous diastolic depolarization of pacemaker cells in the sinus node [17]. The therapeutic role of this drug in the treatment of sinus tachycardia therefore appears logical [18,19], as confirmed in published case reports [9][10][11][12]. The experience with the group of patients in the present study shows that ivabradine can normalize the heart rate in patients with inappropriate sinus tachycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its mode of action is by blocking the "funny" current (If) responsible for spontaneous diastolic depolarization of pacemaker cells in the sinus node [17]. The therapeutic role of this drug in the treatment of sinus tachycardia therefore appears logical [18,19], as confirmed in published case reports [9][10][11][12]. The experience with the group of patients in the present study shows that ivabradine can normalize the heart rate in patients with inappropriate sinus tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from beta-blockers, other potentially effective drugs are nondihydropyridine calcium antag- Springer-Verlag 21-22/2009 wkw Treatment of inappropriate sinus tachycardia with ivabradine onists and amiodarone. Ivabradine, a drug that selectively decreases heart rate, has recently become available; case reports have already shown a favorable response in reported patients [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, ivabradine was reported for its off-label efficacy in cases of inappropriate sinus tachycardia (IST) and postural orthostatic tachycardia syndrome (POTS) [19][20][21]. Cal o et al [22] in a case series that included 18 IST patients demonstrated the effects of ivabradine in reducing HR at the Holter recordings and to increasing the exercise tolerance in stress tests.…”
Section: Inappropriate Sinus Tachycardiamentioning
confidence: 99%
“…However, there is published evidence, albeit from only one case report, of the effectiveness of ivabradine in the treatment of inappropriate sinus tachycardia [Schulze et al 2008].…”
Section: Sinus Tachycardiamentioning
confidence: 99%